Multiparametric functional MRI: a tool to uncover subtle changes following allogeneic renal transplantation - Notohamiprodjo, Mike; Kalnins, Aivars; Andrassy, Martin; Kolb, Manuel Marcus; Ehle, Benjamin; Mueller, Susanna; Thomas, Michael Nikolaus; Werner, Jens; Guba, Markus; Nikolaou, Konstantin; Andrassy, Joachim (PLOS ONE, 2016)
Purpose To investigate multiparametric functional MRI to characterize acute rejection in a murine allogeneic renal transplant model and evaluate the effect of novel therapeutics. Material and Methods We performed allogeneic and syngeneic orthotopic transplantations (Balb/c to C57Bl/6 and C57Bl/6 to C57Bl/6). Allogeneic Groups (n = 5) were either treated with the anti-CCL2-Spiegelmer (mNOX-E36) in monotherapy or in combination with low doses of Ciclosporin-A (10mg/kgBW/d) for 10 days. Controls received equivalent doses of a non-functional spiegelmer (revmNOX-E36) or low dose Ciclosporin-A. Diffusion-weighted (DWI) and Dynamic-contrast-enhanced (DCE-) MRI-scans were performed using a clinical 3T-scanner. DWI analysis (b-values from 0-800 s/mm2) was performed mono- and biexponentially, while DCE-MRI was assessed with deconvolution analysis. Therapy effects were assessed ex vivo with histopathology, immunohistochemistry and RT-PCR. Statistical analysis was performed with unpaired t-tests and Spearman´s correlation coefficient. Results DWI showed a significant diffusion restriction in allogeneic compared to syngeneic transplants (ADC: 0.63±0.08 vs. 1.29±0.12 mm2/s*103) with decreasing diffusion restriction under therapy. DCE-MRI showed restored organ perfusion under Ciclosporin A alone and combination therapy (Plasma Flow: 43.43±12.49; 38.75±7.53ml/100ml/min) compared to syngeneic controls (51.03±12.49ml/100ml/min). Ex vivo analysis showed reduced monocytic infiltrates, attenuated levels of inflammatory cytokines under mNOX-E36 monotherapy with an additive effect of low dose Ciclosporin A. There was a significant (p<0.05) negative correlation between ADC and interstitial inflammation (r = -0.73) or macrophage infiltration (r = -0.81) and between organ perfusion and intimal arteritis (r = -0.63). Conclusion Multiparametric functional MRI is suited to detect renal allograft rejection in an experimental murine model and allows to characterize effects of immunosuppressive therapy alleviating acute rejection processes in allogeneic transplantation.